THE FACTORS AFFECTING THE ADOPTION OF A WELL-INTEGRATED INTERNET BANKING SYSTEM IN MAURITIUS - Sunecher, Yuvraj; Ramphul, Needesh; Chittoo, Hemant; Poolay, Kamlesh Singh (Bank Indonesia, 2024)
As the result of technological advancements, online banking is becoming a major feature for banks because it helps customers to save time and benefits banks financially. Although Mauritius’s banking sector is well developed, its e-banking sector has lagged behind other countries. Hence, the purpose of this study is to identify the factors affecting the adoption of internet banking. From the findings of the study, it can be seen that many Mauritians nowadays use internet banking, but it is principally the new generation whereas the older banking customers prefer the traditional way as they do not trust the internet to manage their money. Also, though many use e-banking now they still think human contact is important for banking relation and continue to visit their banks, thus proving that even if online banking is in well integrated in Mauritius now, it still has a long way to go for Mauritians to integrate it into their everyday lives and use it to its full potential.